Ultra performance liquid chromatography mass spectrometry : evaluation and applications in food analysis - Naushad, Mu (CRC Press, 2014)
"The development of many novel techniques that make our existence so comfortable has been intimately associated with the accessibility of suitable analytical methods. Liquid chromatography-mass spectrometry (LC-MS) is a powerful technique used for various applications based upon its very high sensitivity and selectivity. Generally, its applications are oriented toward the detection and identification of chemicals in a complex mixture. Preparative LC-MS systems can be used for fast and mass-directed purification of natural product extracts and new molecular entities important to food, pharmaceutical, agrochemical, and other industries. This book presents a unique collection of up-to-date UPLC-MS/MS (ultra performance liquid chromatography-tandem mass spectrometric) methods for the separation and quantitative determination of pesticides, capsaicinoids, heterocyclic amines, aflatoxin, perfluorochemicals, acrylamide, procyanidins and alkaloids, lactose content, phenolic compounds, vitamins, and aroma and flavor compounds in a wide variety of foods and food products. This book is the result of the remarkable contributions of 35 experts in interdisciplinary fields of science, with comprehensive, in-depth, and up-to-date research works and reviews. Composed of 16 chapters and compiled using more than 78 figures and 50 tables, this text delivers practical information to all people involved in the research and development, production, or routing analysis of foods and food products. Mu. Naushad and M.R. Khan Editors"-- Provided by publisher.
Keywords: Food -- Analysis.; Food additives -- Analysis -- Methodology.; High performance liquid chromatography.; Mass spectrometry.; elektronické knihy; electronic books